2008
DOI: 10.1103/physrevb.77.125401
|View full text |Cite
|
Sign up to set email alerts
|

Phonon dispersions and vibrational properties of monolayer, bilayer, and trilayer graphene: Density-functional perturbation theory

Abstract: The phonon dispersions of monolayer and few-layer graphene (AB bilayer, ABA and ABC trilayers) are investigated using the density-functional perturbation theory (DFPT). Compared with the monolayer, the optical phonon E2g mode at Γ splits into two and three doubly degenerate branches for bilayer and trilayer graphene, respectively, due to the weak interlayer coupling. These modes are of various symmetry and exhibit different sensitivity to either Raman or infrared (IR) measurements (or both). The splitting is f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
190
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(224 citation statements)
references
References 48 publications
(75 reference statements)
31
190
0
3
Order By: Relevance
“…Detailed analysis of LO and TO modes regarding their vibrational properties and couplings to electronic states leading to Kohn anomaly were also reported. 21,22 Upon the coverage of ⌰ =1/ 8 of CЈ the D 6h symmetry of graphene turns into the C 2v ͑or mm2͒ point group. It is seen from Fig.…”
Section: A Stability and Migration Of Carbon Adatomsmentioning
confidence: 99%
“…Detailed analysis of LO and TO modes regarding their vibrational properties and couplings to electronic states leading to Kohn anomaly were also reported. 21,22 Upon the coverage of ⌰ =1/ 8 of CЈ the D 6h symmetry of graphene turns into the C 2v ͑or mm2͒ point group. It is seen from Fig.…”
Section: A Stability and Migration Of Carbon Adatomsmentioning
confidence: 99%
“…20 It was found that the electron and hole bands touching at zero energy support chiral quasiparticles characterized by a Berry phase of Nπ for N layers. The phonon spectrum of ABC-stacked graphene has been investigated theoretically using density functional theory 21 and experimentally by using infrared absorption spectroscopy, where the intensities have been found to be much stronger than that of bilayer graphene. 22 Using magnetic fields up to 60 T, there has been evidence of the integer quantum Hall effect in trilayer graphene.…”
mentioning
confidence: 99%
“…Among the most used computational approaches we can mention the elastic continuum model [97,98], the first principles DFT also with Perdew-BurkeErnzerhof generalized gradient approximation [99][100][101], and the molecular dynamics simulations associated with the use of empirical interatomic potentials for the interactions between carbon atoms, which allows to treat larger systems [102]. The most effective have been demonstrated the Long-range Carbon Bond-Order Potential (LCBOPII) [103] and the parameterization by Lindsay et al [104].…”
Section: Dynamical Morphingmentioning
confidence: 99%